2019
DOI: 10.1080/14767058.2019.1633303
|View full text |Cite
|
Sign up to set email alerts
|

Fetal abdominal wall defects in an Australian tertiary setting: contemporary characteristics, ultrasound accuracy, and outcome

Abstract: Fetal abdominal wall defects in an Australian tertiary setting: contemporary characteristics, ultrasound accuracy and outcome PurposeIn this study we aimed to comprehensively evaluate risk factors, ultrasound estimation of fetal weight, prenatal management and pregnancy outcomes of gastroschisis and omphalocele at a metropolitan Australian hospital. Material and MethodsThis was a retrospective single centre cohort study from 2006 to 2014 at a tertiary hospital with co-located neonatal surgical facilities. Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…For omphalocele, the number of associated malformations ranges from 27% to 63%, and for gastroschisis, it ranges from 5% to 27%. 16,17 In a different study, 98 cases diagnosed with omphalocele in the first trimester were evaluated. 18 It was observed that 45.9% of the cases had major structural anomalies, and 53.8% had chromosomal anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For omphalocele, the number of associated malformations ranges from 27% to 63%, and for gastroschisis, it ranges from 5% to 27%. 16,17 In a different study, 98 cases diagnosed with omphalocele in the first trimester were evaluated. 18 It was observed that 45.9% of the cases had major structural anomalies, and 53.8% had chromosomal anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of associated anomalies determines the prognosis of omphalocele and gastroschisis. For omphalocele, the number of associated malformations ranges from 27% to 63%, and for gastroschisis, it ranges from 5% to 27% 16,17 . In a different study, 98 cases diagnosed with omphalocele in the first trimester were evaluated 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study by Di Filippo et al 24 . compared sonographic EFW in fetuses with AWDs using both the Hadlock I and II formulae and the Siemer formula.…”
Section: Discussionmentioning
confidence: 99%